The transmission of foreign shocks to South Eastern European economies - Petrevski, Goran; Bogoev, Jane; Tevdovski, Dragan (Springer Science and Business Media LLC, 2014)
This paper investigates the transmission of foreign shocks to economic activity and macroeconomic policies in three South Eastern European (SEE) economies: Croatia, Macedonia and Bulgaria. Specifically, we provide empirical evidence on the influence of several policy and non-policy shocks (euro-zone output gap, money market rate and inflation) on economic activity as well as monetary and fiscal policies in the three countries. The main motivation behind our empirical investigation is the fact that all of these economies are small open economies with rigid exchange rate regimes and different degree of integration within the European Union (EU). As for the methodological issues, we employ recursive vector autoregressions to identify the exogenous shocks in the euro-area. Generally, the estimated results imply that euro-zone economic activity has significant and relatively strong influence on these economies where foreign output shocks are transmitted relatively quickly. The results also suggest that the effects of foreign shocks are of larger magnitude in the countries that are more integrated with the EU. An additional finding is that positive foreign interest rate shocks trigger a contractionary response of domestic monetary policy notwithstanding the fact that domestic money market rates are not linked with euro-zone interest rates. Finally, euro-zone inflation is instantly transmitted to domestic inflation. We can explain these effects by several factors, such as: the fixed exchange rates, the relatively high trade integration of SEE economies within the euro-zone as well as the dependence of SEE banks on foreign financing.
Keywords: Monetary policy, Vector autoregression, Exogenous shocks